Solution phase synthesis and intense pulsed light sintering and reduction of a copper oxide ink with an encapsulating nickel oxide barrier. (1st May 2015) - Jha, M; Dharmadasa, R; Draper, G L; Sherehiy, A; Sumanasekera, G; Amos, D; Druffel, T
Abstract Copper oxide nanoparticle inks sintered and reduced by intense pulsed light (IPL) are an inexpensive means to produce conductive patterns on a number of substrates. However, the oxidation and diffusion characteristics of copper are issues that must be resolved before it can be considered as a viable solution. Nickel can provide a degree of oxidation protection and act as a barrier for the diffusion of copper. In the present study we have for the first time synthesized copper oxide with an encapsulating nickel oxide nanostructure using a solution phase synthesis process in the presence of a surfactant at room temperature. The room temperature process enables us to easily prevent the formation of alloys at the copper–nickel interface. The synthesis results in a simple technique (easily commercializable, tested at a 10 g scale) with highly controllable layer thicknesses on a 20 nm copper oxide nanoparticle. These Cu2O@NiO dispersions were then directly deposited onto substrates and sintered/reduced using an IPL source. The sintering technique produces a highly conductive film with very short processing times. Films have been deposited onto silicon, and the copper-nickel structure has shown a lower copper diffusion. The nanostructures and resulting films were characterized using electron and x-ray spectroscopy, and the films' resistivity was measured.